2022
DOI: 10.1021/acs.jpca.1c10970
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic Coupling in Spherically Encapsulated, Diatomic Molecules: Prediction of a Renner–Teller-like Effect for Endofullerenes

Abstract: In the year 1933, Herzberg and Teller realized that the potential energy surface of a triatomic, linear molecule splits into two as soon as the molecule is bent. The phenomenon, later dubbed the Renner–Teller effect due to the detailed follow-up work of Renner on the subject, describes the coupling of a symmetry-reducing molecular vibration with degenerate electronic states. In this article, we show that a very similar type of nonadiabatic coupling can occur for certain translational degrees of freedom of diat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…A significant decrease in the hyperfine coupling constant of boron was reported in the cage compared to its free state. In a recent study, taking NO encapsulated fullerene NO@C 60 as the model system, Hauser and Pototschnig theoretically predicted Renner–Teller-like vibronic coupling in the electronically degenerate heteronuclear diatomic molecule under spherical confinement …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant decrease in the hyperfine coupling constant of boron was reported in the cage compared to its free state. In a recent study, taking NO encapsulated fullerene NO@C 60 as the model system, Hauser and Pototschnig theoretically predicted Renner–Teller-like vibronic coupling in the electronically degenerate heteronuclear diatomic molecule under spherical confinement …”
Section: Introductionmentioning
confidence: 99%
“…Despite significant progress in the theoretical understanding of various nonmetal paramagnetic species based on fullerene, a systematic theoretical exposition of host–guest interaction between NO and fullerene C 60 has not been carried out. We also note that although several studies are reported about the adsorption of NO over different carbonaceous materials, the adsorption of NO on fullerene-based materials is rarely addressed in the literature. , The present study focuses on the systematic theoretical investigations of the electronic structure, stability, and noncovalent interaction present in NO@C 60 and NO.C 60 complexes with the aid of the quantum theory of atoms in molecules (QTAIM), , noncovalent interactions (NCI), and molecular electrostatic potential (MESP) analyses . Furthermore, a detailed theoretical analysis of the interactions of two NO radicals with C 60 , their energetics, and structural properties at various locations of NO are discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This definition of ε has been widely used in characterizing the RT effect, even till today. , For an extension, very recently, it was shown that the NO molecule encapsulated in a fullerene can also experience a vibronic coupling effect very similar to the RT effect regarding the NO translation . Thus, the RT parameter may not only characterize the distortion of linear molecules but also quantify energy splitting of more complex systems.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting electronic effects such as vibronic couplings will be explored in future work. 40 The results presented here show a rather small energy splitting of 1−2 K between the first two oppositely polarized states, which might suggest a comparably low Curie temperature of a few Kelvin. However, this temperature strongly depends on the density of states and the polarization of the excited states.…”
mentioning
confidence: 99%